Socio-Ecological Conservation in the Architecture of Kampung Adat Dukuh: A Critical Study Approach Based on Lawrence and Barrie - Pramesti, Cipto Surya; Husnan, Cecep; Dapik, Zalma; Yuyus, Yuyus; Manap, Dudung Abdul; Nurholis, Egi (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
This study discusses socio-ecological conservation in the architecture of Kampung Adat Dukuh through a critical review of the theories of Roderick J. Lawrence (2000) and Thomas Barrie (2017). Kampung Adat Dukuh, as a cultural heritage site, has interrelated ecological and social values that play an important role in the sustainability of the ecosystem and local culture. However, modernization and development pressures threaten the sustainability of its architecture and socio-ecological harmony. This study employs a qualitative approach using in-depth interviews, field observations, documentation, and thematic and critical data analysis. The research findings indicate that architectural conservation in the Dukuh Traditional Village must balance traditional values and contemporary development needs while simultaneously considering ecological and social dimensions. Lawrence and Barrie’s study emphasizes the importance of a holistic and dialogical approach in cultural and ecological conservation. The implications of this research provide strategic recommendations for adaptive and sustainable traditional village preservation policies in the modern era.